Exploring Purchase Intention in Online Influencer Marketing Campaigns Through an Integrated Model - Shu Liu (SAGE Open)
Social media offer a digital space for people to connect with online influencers, such as bloggers, YouTubers, and Instagram celebrities. This study aims to investigate the factors affecting consumers’ purchase intention in social media-based influencer marketing context, while simultaneously revealing the underlying mechanisms through an integrated model. An online survey with 335 participants who have followed social media influencers (SMIs) was conducted to empirically test our proposed model. PLS-SEM was employed to analyze the measurement and structural models. The findings indicate that SMIs, when perceived as credible sources exhibiting high levels of expertise, trustworthiness, and homophily, stimulate consumers’ fear of missing out (FOMO) and establish parasocial relationships with these influencers, which in turn enhance purchase intention. Furthermore, when consumers perceived a high level of serendipity, the relationship between FOMO and purchase intention will be strengthened. This study extends the perspective of source credibility and parasocial relationships in the context of influencer marketing by incorporating the impact of smart recommendation algorithms and the emotional anxiety experienced by consumers. It offers a novel approach to analyze why consumers are motivated to purchase products endorsed by SMIs.